2010
DOI: 10.1051/agro/2009013
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and pest management in orchard systems. A review

Abstract: Conventional agriculture is based on a high level of chemical inputs such as pesticides and fertilisers, leading to serious environmental impacts, health risks and loss of biodiversity in agrosystems. The reduction of pesticide use is a priority for intensively sprayed agricultural systems such as orchards. The preservation and promotion of biodiversity within orchards and their boundaries is therefore an issue to explore. Indeed, orchard systems contain high plant diversity and perennial multi-strata designs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
115
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(125 citation statements)
references
References 125 publications
(159 reference statements)
0
115
0
5
Order By: Relevance
“…In their research on dicotyledonous weeds, Wilson & Aebisher (1995) reported that the density of most arthropod species decreased significantly as distance from crop edge increased from 0 to 128 m. Some authors (Winkler, 2005;Bàrberi et al, 2010) have reviewed the importance of vegetation diversity for enhancing populations of beneficial arthropods in cropland. Wyss (1996), Simon et al (2010) and Song et al (2010) reported a positive effect of plant comunity diversification on beneficial arthropods in orchards. Non-crop habitats bordering agricultural fields in Europe have been found to have a favourable effect on a number of beneficials as spiders, ladybugs, and syrphids (Hillocks, 1998;Ernoult et al, 2013).…”
Section: Plant Comunitiesmentioning
confidence: 97%
“…In their research on dicotyledonous weeds, Wilson & Aebisher (1995) reported that the density of most arthropod species decreased significantly as distance from crop edge increased from 0 to 128 m. Some authors (Winkler, 2005;Bàrberi et al, 2010) have reviewed the importance of vegetation diversity for enhancing populations of beneficial arthropods in cropland. Wyss (1996), Simon et al (2010) and Song et al (2010) reported a positive effect of plant comunity diversification on beneficial arthropods in orchards. Non-crop habitats bordering agricultural fields in Europe have been found to have a favourable effect on a number of beneficials as spiders, ladybugs, and syrphids (Hillocks, 1998;Ernoult et al, 2013).…”
Section: Plant Comunitiesmentioning
confidence: 97%
“…Planting orchards is a long-lasting tradition in temperate areas and they belong to perennial crops, therefore, this is a reason why orchards are regarded as a highly stable, predictable habitat for many organisms (Brown and Welker 1992;Koza´r 1992). The multi-strata design of orchards and the presence of adjacent weeds and hedges contribute to diversity of arthropods and birds (Rands 1986;Kwiatkowska 1989;Simon et al 2010). In addition, a high abundance of flowers and fruits constitute an excellent source of food for pollinating insects.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, pests and diseases that are host-tree permanent may remain in the orchard for many years and require continuous control. Due to this effect, orchards are among the most intensively sprayed agricultural systems, in order to avoid visible and internal fruit damage and to satisfy international commercial quality standards [50]. The main environmental risks relating to the use of conventional pesticides are the negative effects on the animal and plant communities exposed both in the orchard and in the other terrestrial and aquatic ecosystems to which pesticides are lost [51].…”
Section: The Environmental Demand Of Fruit Production Systemsmentioning
confidence: 99%